2014
DOI: 10.1021/am5049543
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Ultrathin Nanocomposite Polymer Films Controlled by the Embedding of Gold Nanoparticles

Abstract: Thin and ultrathin polymer films combined with nanoparticles (NPs) are of significant interest as they are used in a host of industrial applications. In this paper we describe the stability of such films (hpoly ≤ 30 nm) to dewetting, specifically, how the development of a spinodal instability in a composite NP-polymer layer is controlled by the embedding of Au NPs. At working temperatures (T = 170 °C) above the polymer glass transition temperature (Tg ≈ 100 °C) the absence of Au NPs leads to film rupture by nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 36 publications
(211 reference statements)
1
38
0
Order By: Relevance
“…Amarandei et al . revealed that Au nanoparticles, whose surface energy is higher than that of PS, on the surface of PS ultrathin film with thickness of less than 30 nm were embedded in the film during thermal annealing above the glass‐transition temperature of PS, similarly to oleic acid‐modified CeO 2 nanoparticles in this work.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Amarandei et al . revealed that Au nanoparticles, whose surface energy is higher than that of PS, on the surface of PS ultrathin film with thickness of less than 30 nm were embedded in the film during thermal annealing above the glass‐transition temperature of PS, similarly to oleic acid‐modified CeO 2 nanoparticles in this work.…”
Section: Resultssupporting
confidence: 59%
“…From the above results, it was found that the nanoparticles at the surface of the PS nanocomposite thin film migrate through the film to the substrate surface during thermal annealing, regardless of the nanoparticle concentration and film thickness. However, there Amarandei et al 33 revealed that Au nanoparticles, whose surface energy is higher than that of PS, on the surface of PS ultrathin film with thickness of less than 30 nm were embedded in the film during thermal annealing above the glass-transition temperature of PS, similarly to oleic acid-modified CeO 2 nanoparticles in this work. They proposed a criterion for determining whether the nanoparticles are embedded in the films, being based on their free energy, which is controlled by the interaction of nanoparticles with the underlying polymer and substrate.…”
Section: Resultsmentioning
confidence: 48%
“…Fig. 7(b) shows the high resolution XPS spectrum of C1s consisting of two main peaks at around 283.29 eV and 284.57 eV which correspond to SiC (C Si bonding) and surface adsorbed organic contaminants (C C/C C/C H bonding) [40][41][42][43], respectively. No significant changes were observed to indicate any reaction between SiC nanorods and Au/Pd coating.…”
Section: Resultsmentioning
confidence: 99%
“…The physical and chemical properties of nanocomposites, consisting of organic (e.g., polymer) and inorganic (e.g., metal) building blocks, are of considerable interest both from a fundamental point of view 1,2 and for potential applications. [3][4][5][6][7] One of the very widely used techniques to fill a polymer with metal is evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, however, this is not always the case resulting in NPs resided on polymer surfaces. 1,15,16 Penetration of NPs certainly requires long-range polymer chain mobility, thus, no or partial immersion can be expected at temperatures below glass transition (< T g ), whereas for temperature above T g complete NP embedding in the polymer film can be observed. 8,10,17 Metal NPs have also been deposited from solutions directly onto a polymer surface, where NP immersion is driven by the formation of a thin wetting layer.…”
Section: Introductionmentioning
confidence: 99%